Floating Cities from Concept to Creation :Neighbourhood Guide to the Future Development - Saloni Goyal; Ananya Jain (International Journal of Urban Design and Development, 2023)
Today cities are overpopulated and only 40% of space is left to house the world's population by 2050. Due to ever rising sea level 90% of coastal cities will be affected by flooding by the end of the century. This research aims to study about the floating city as a substitute. Floating cities shape to construct all of the infrastructure required for a water-based metropolis while also providing contextual space for humans Additionally, the concept inspired the use of marine vitality assets and incorporated them into the design. In depth, literature study was conducted for analyzing the parameters related to social and environmental challenges; for identifying the needs of different resources. Based on the findings related to rising sea-level and submerging coastline a detailed case study is done to validate the possibilities of the existence of floating cities in future; to acquire the requirements needed by the people living in and to understand the relative importance of energy alternatives for day-to-day need. Development of floating city requires modern innovation, social and community information. The combination of these factors gave rise to the concept of widening urban access to water-based space. The thought of living by water itself is a new form of urbanization. Assessment of the key characteristics of a floating city that significantly affects alternative renewable energy sources and the world's energy supplies. Implementing contemporary innovation and sharing social and community information are essential to the growth of the floating city. This research shows that floating structures can be an interesting solution to integrate ocean energy resources and floating design This extensive literature review provided useful insights and a closeup lens of upcoming challenges for floating city and their solution.
Keywords: Climate change; Floating cities; resources; rising sea level; transportation